Налогообложение операций взаимосвязанных лиц: российско-украинский опыт - Тимарцев, А.Ю. (Культура народов Причерноморья, 2013)
В статье дана критическая оценка правил контроля за трансфертными ценами, в основе которых лежит общий «принцип вытянутой руки». Обобщена практика функционирования в системе налоговых органов РФ специальной налоговой инспекции по контролю над ценами. Обоснована целесообразность введения в практику украинского налогообложения принципа консолидированного налогообложения связанных лиц и симметричных корректировок. У статті дана критична оцінка правил контролю за трансфертними цінами, в основі яких лежить загальний "принцип витягнутої руки". Узагальнено практику функціонування в системі податкових органів РФ спеціальної податкової інспекції з контролю над цінами. Обґрунтовано доцільність введення в практику українського оподаткування принципу консолідованого оподаткування пов'язаних осіб і симетричних коригувань. The critical estimation of new rules of control over transfer prices, which are based on a general “arm’s length principle”, is given in the article. The Russian and Ukrainian legislation adheres to the principle that transactions between related parties must be carried out according to market (ordinary) prices. The Tax Code contains the methodical approach of their calculation in order to stop the abuse of external transfer prices for diminishing the tax burden. The practice of functioning the special price control tax office in the system of tax authorities of the Russian Federation is summarized. The wisdom of applying the principle of the consolidated taxation of the related parties and symmetric adjustments in the Ukrainian taxation is substantiated. The legal framework of creating the consolidated group is signing the corresponding agreement and preliminary conforming the basic terms of agreements, having signs of the related party transactions, with the tax authorities, that will allow avoiding conflict situations while explaining by the payer the tax of transfer prices.